Awareness, attitude, and utilization of psychological counselling and guidance among undergraduates at the University of Jaffna - Samarasinghe, K.; Ranathunga, Y.; Kamalarupan, L.; Thabotharan, K. (University of Jaffna, 2023)
Introduction: Psychological counselling and guidance is a recently discovered, modern way of solving problems. Most of the time, it involves clarifying matters and showing possibilities to the client. Objective: To assess the awareness, attitude, and utilization of psychological counselling and guidance among undergraduates at the University of Jaffna. Methodology: This institute-based descriptive cross-sectional study was conducted among 426 undergraduates of the University of Jaffna. Data was collected using a self-administered questionnaire and SPSS 25 software was used to analyse the data. Descriptive statistical test; mean, frequency, percentages were used to analyse the data. Five faculties were selected by convenience sampling method and participants were selected from each faculty by proportionate random sampling method. Results: University students (87.4%) were aware of the University counselling services and guidance. The majority (42.9%) got this awareness through their orientation programmes. Many (32.5%) approached counsellors for academic problems. Among them (78.9%) believed university counselling was a good service and was important to release their stressors (25.2%). However, (94.3%) of participants had never utilized the University counselling system. Only a few (5.7%) were used. Some (45.5%) were not satisfied with the service offered. Conclusion: The majority of the participants were aware of university counselling services at A positive attitude was observed among participants towards counselling services. Although the counselling centre offers a variety of services, most of the participants were not aware of it and those who used the counselling services were less.
Keywords: Awareness; Attitude; Utilization; Psychological counselling; Guidance